A qualitative study on the perceived impact of using an integrated community‐based supportive cancer service. (8th February 2019) - Young, Jenny; Snowden, Austyn
Abstract: Objective: "Improving the Cancer Journey" (ICJ) is an original, community‐based, multidisciplinary service offering holistic support to people diagnosed with cancer in Scotland. It is the first service of its kind in the UK. The aim of this qualitative study was to explore the experiences of people who have used this service. Method: Twenty service users were purposively sampled to capture a diverse range of age, sex, cancer types, and deprivation status. Semi‐structured interviews explored their experiences of using ICJ. Interviews were transcribed verbatim and thematically analysed. Results: Thirteen women and seven men (mean age 58 years) were interviewed. Three themes were identified: "one person, one place, " "routes to unexpected support" and "safety net." Conclusion: Improving the Cancer Journey was perceived to be beneficial because it met the holistic needs of the ICJ service users. By helping people address concerns earlier rather than later, it prevented problems becoming unmanageable. Having an accessible expert to guide and support them through a range of services provided reassurance and created the space to self‐manage at a time of distress. These original findings are internationally relevant because there is little evidence on the impact of holistic support services from the patient perspective.